KONDISI HABITAT BULU BABI Tripneustes gratilla (LINNAEUS, 1758) DI TELUK CENDERAWASIH - Abdul Hamid A. Toha; Sutiman B. Sumitro; Luchman Hakim; Widodo (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2012)
The primary goal of this research was determine physical and chemistry conditions of habitat of Tripneustes gratilla at Cenderawasih Bay waters. Sites of research were Manokwari, Wasior, Biak, Yapen and Nabire. Habitat of T. gratilla was observed directly with determine of temperature, salinity, velocity of current, pH, and dissolved oxygen by using thermometer, saline refractometer, pH-meter and DO-meter. We found that habitat of T. gratilla has temperature range of 30-31° C, salinity 30–32o/oo, pH 7.3-8.0, DO 4.9–8.7 mg/L, wave frequency 0.32-0.72 Hz, and current velocity 0.06-0.1 m/sec. Statistic test showed that T. gratilla were impacted by DO about 80% and wave frequency with 66%. In general, habitat of T. gratilla in Cenderawasih Bay were in good condition and supporting growth, develop and survival of T. gratilla.